El juez de vigilancia penitenciaria en España, como referente de la ejecución penal en América Latina (2018)
Although prison is the oldest and most oppressive penalty that has been implemented in the world, unfortunately there is still no penalty that can replace its exercise and function, penitentiary surveillance judges are the ones who exclusively enforce what is sentenced in the exercise of the jurisdictional power, and thus comply not only with the judicial order determined in a sentence but they also comply with what is stipulated in the constitutional mandate and becomes automatic in a body that guarantees the rights of persons deprived of liberty, having the great task of vindicating the legal-state function of penitentiary institutions. It is of the utmost importance to analyze the creation and function of this figure within the penitentiary system in Spain, which has served as an example for Latin American countries such as Mexico and Colombia, and has set the standard for the establishment of a modern model of criminal enforcement.